Enantioselective biodegradation and enantiomerization of dichlorprop in soils. (November 2020) - Youfeng, Zhu; Dongdong, Zhang; Ling, He
Abstract: The dissipation of racemic, R-, and S- dichlorprop (DCPP) in four soils were studied in the laboratory. The half-lives of racemic DCPP were from 10.5 to 19.8 days. Preferential degradation of R- or S-DCPP was detected in all soils, even in one soil that the apparent enantiomeric fraction remained constant during incubation. The enantiomerization of DCPP was found to proceed in both directions, except in forest soil that no enantiomerization of S- to R-DCPP was observed. The isomerization equilibrium constant (K = kRS /kSR ) in two vegetable soils were 0.54 and 0.53, respectively, favoring herbicidally active R enantiomer, while in paddy soil K was 1.60, favoring an inversion of R into S enantiomer. Real-time PCR showed that the rdpA gene was not detected in all indigenous and DCPP amended microcosms probably because of relative short incubation time and low amendment concentrations. In contrast, the sdpA gene was present in indigenous soils and significantly elevated after DCPP addition with the highest relative abundance around day 10 in all microcosms. Illumina sequencing of the 16S rRNA gene showed that the relative abundance of Proteobacteria significantly increased in all DCPP treated soils. DCPP-degrading related families, Sphingomonadaceae and Comamonadaceae, enhanced in all soils, while Burkholderiaceae elevated only in paddy soil with preferential degradation of S-DCPP and Pseudomonadaceae only in forest soil with R-enantiomer preference. The sdpA gene sequencing revealed that about 92%–99% of bacteria harboring sdpA genes in studied soils belong to Alphaproteobacteria . Highlights: Both enantioselective degradation and enantiomerization contributed enantioselectivity of DCPP in soils. DCPP-degrading related families Sphingomonadaceae and Comamonadaceae enhanced in all DCPP added soils. More than 92% of bacteria harboring sdpA genes belong to Alphaproteobacteria.